FERTILITY: THE MALE ASPECT - Trishkin, Aleksey Gennadievich; Shadrintsev, Vladimir Alexandrovich; Plavko, Marina Nikolaevna; Еlgina, Svetlana Ivanovna; Rudaeva, Elena Vladimirovna; Moses, Vadim Gelievich; Shmelev, Alexey Andreevich; Bochkarnikova, Asmik Gerbertovna; Moses, Kira Borisovna (Mother and Baby in Kuzbass, 2026)
A man's ability to fertilize (fertility) is directly dependent on the coordinated functioning of the reproductive tract organs responsible for the production and transport of male reproductive cells. Fertility indicators exhibit a high degree of variability due to natural factors such as the frequency of sexual activity, age-related changes, heredity, and phenotypic characteristics. An analysis of fertility indicators by age group revealed a negative correlation between a man's age and the molecular and functional characteristics of his sperm in cases of infertility. Age is a contributing factor to the increase in DNA damage and the decrease in the pool of mature gamete forms. The most significant negative changes occur in the age group over 40. This fact should be taken into account when creating personalized diagnostic algorithms and planning preconception preparation.
Keywords: infertility; fertility; ART